Pesticide Residues in Fresh Water Fishes of Saurashtra Region - A.A., Zynudheen; A.G., Radhakrishnan (Fishery Technology, 2025)
Pesticide residues in fresh water fishes from different sources of Saurashtra region in Gujarat were estimated. Periodic samples were collected from the retail markets, and pesticides estimated by Varian GC 3700. The levels of pesticides varied in different samples collected during same period and in the same species collected during different periods. The samples from Rajkot fish market contained higher level of pesticides compared to the samples from Junagadh. However, the pesticides detected in the samples were well below the permitted levels.